Abstracts presented during the 12th Scientific Conference of The Muhimbili University of Health and Allied Sciences (Tanzania Medical Journal, 2024)
The Muhimbili University of Health and Allied Sciences (MUHAS) held its 12th Scientific Conference on 27th & 28th July 2024, at the East African Centre of Excellence for Cardiovascular Sciences, MUHAS Mloganzila Campus, Dar es Salaam. The conference Theme was: “Science as a story of Life: The Power of Research, Innovation, and Collaboration in Improving the Resilient Health systems”, with Subthemes; Traditional and Alternative Medicine, Drug Discovery, and Vaccine Development; Maternal, Newborn, Child and Adolescent Health; Non-Communicable Diseases, Mental Health, Surgery and Nutrition; Health Systems Research; Oral, Eye, ENT Health and Care; Communicable Diseases and Antimicrobial Resistance; Social Determinants for Health and Cross-cutting issues. Tanzania Medical Journal expressed its readiness to collaborate with the organizing committee of this successful conference in publishing abstracts presented during the conference. The abstracts are presented in their respective subthemes. The scientific sub-committee for this conference was responsible for the peer review of the abstracts.